2019
DOI: 10.1107/s2059798319008131
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the transcriptional regulator BgaR, a lactose sensor

Abstract: The structure of BgaR, a transcriptional regulator of the lactose operon in Clostridium perfringens, has been solved by SAD phasing using a mercury derivative. BgaR is an exquisite sensor of lactose, with a binding affinity in the low-micromolar range. This sensor and regulator has been captured bound to lactose and to lactulose as well as in a nominal apo form, and was compared with AraC, another saccharide-binding transcriptional regulator. It is shown that the saccharides bind in the N-terminal region of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Intact mass determination of kifunensine-treated, affinitypurified hENPP1-HIS samples was achieved by LC-MS as described previously (Newman et al, 2019). N-linked glycoprofiling was achieved by hydrophilic liquid chromatography with fluorescence and mass-spectrometry readouts (HILIC-FL-MS).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Intact mass determination of kifunensine-treated, affinitypurified hENPP1-HIS samples was achieved by LC-MS as described previously (Newman et al, 2019). N-linked glycoprofiling was achieved by hydrophilic liquid chromatography with fluorescence and mass-spectrometry readouts (HILIC-FL-MS).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Unlike the well-conserved C-terminal DNA binding domain, the N-terminal domains of AraC proteins, usually encoding dimerization and/or ligand binding sites (33,38), do not share much similarity at the amino acid level. However, careful analyses of predicted secondary structures of the N-terminal domains of AraC proteins and crystal structures of AraC (39), ToxT (44), ExsA (53), and BgaR from Clostridium perfringens (55) have revealed a conserved structure. Importantly, these proteins contain a hydrophobic ␣-helix at the end of the N-terminal domain that has been shown to be critical for dimer formation in AraC (39, 56), ToxT (44, 57), XylS of Pseudomonas putida (58), and ExsA (51).…”
mentioning
confidence: 99%
“…The only AraC-type transcriptional regulator of a β-galactosidase gene that has been characterized at the molecular level is BgaR of the gram positive Clostridium perfringens [ 56 , 57 , 58 ], which has been demonstrated to be regulated by lactose and partially lactulose, but not by IPTG. On the other hand, we have clearly demonstrated that pP79 induction is mainly mediated by IPTG.…”
Section: Figure A1mentioning
confidence: 99%